Functionalisation of AgInS2/ZnS TQDs with 4-aminophenyl boronic acid for the development of a spectrofluorometric method for digoxin determination in pharmaceutical samples - Jose A. Rodriguez; Alfredo Guevara-Lara; Carlos Ángel-Jijón; Raybel Muñoz (Results in Chemistry, 2025)
A novel spectrofluorometric method for digoxin sensing in pharmaceutical samples was developed using AgInS2/ZnS ternary quantum dots functionalized with 4-aminophenylboronic acid. Synthesized quantum dots were characterized by UV–Vis, fluorescence, FTIR, 11B NMR and transmission electron microscopy. The boronic acid functionalized on the nanoparticle surface forms a complex with digoxin at high pH values leading to the aggregation of the nanoparticle and the quenching of the fluorescence at 558 nm, the difference in the analytical signal is used to obtain the calibration curve for digoxin determination. Proposed method exhibits optimal analytical parameters: detection limit of 1.90 μM, a linear range from 5.70 to 80.00 μM, appropriate repeatability, reproducibility (%RSD <5.0 %) and adequate selectivity for digoxin in the pharmaceutical samples evaluated. The developed method was validated using a t-test for equal variances by comparing the mean concentration digoxin obtained of samples analysed by triplicate to the mean of a HPLC-UV methodology, resulting in an adequate accuracy. Spectrofluorometric methodology was applied for the determination of digoxin of 3 pharmaceutical formulations and concentrations found in the samples were in the range of 242.98–250.63 μg per tablet exhibiting an adequate performance for pharmaceutical matrices. Use of AgInS2/ZnS functionalized with 4-APBA are a suitable strategy for digoxin analysis in pharmaceutical based on the stability of the nanoparticle, the optimal analytical parameters, and the rapidness of the method. These novel nanomaterials have significant potential for the development of optical and visual sensors and finding merit additional research for its application in more complex matrices such as biological.